Practical residual stress measurement methods - Schajer, Gary S. (Chichester, West Sussex, United Kingdom : John Wiley & Sons Inc., 2013)
"This comprehensive collection of practical residual stress measurement techniques is written by world-renowned experts in their respective fields. It provides the reader with the information needed to understand key concepts and to make informed technical decisions. Fully illustrated throughout, each chapter is written by invited specialists and presents chapters on hole-drilling and ring-coring, deep hole drilling, slitting, contour method measurements, X-ray/synchrotron/neutron diffraction, ultrasonics, Barkhausen noise and optical measurement techniques"--
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2021. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Residual stresses; Electronic books